Factors impacting professional accounting students' satisfaction with distance learning: evidence from a Malaysian public university / Nazreen Sahol Hamid … [et al.] - Sahol Hamid, Nazreen; Johari, Razana Juhaida; Mam Yudi, Melissa; Hashim, Afizah; Abd Talib, Norli; Sukirno, Sukirno (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2023)
Distance learning is a means for delivering teaching through the internet, with the use of various technologies and resources to provide material and engage students. This study examined students’ perceptions of the opportunities and difficulties of distance learning, as well as their satisfaction with a distance learning experience. The data was gathered from a public university in Malaysia and analyzed using Partial Least Squares (PLS) structural equation modeling. The results revealed in terms of the students’ perceived opportunities for distance learning, ICT skills and lifelong learning had a significant effect on how satisfied students are with distance learning, while the educational structure hadno significant effect. In terms of perceived challenges, students saw plagiarism and deviation from the primary goal as having a major impact on their satisfaction, but not the educational expenses. The findings aid institutions in providing better knowledge for the development of future distance learning programs for accounting qualification and provide a better understanding of the success of distance learning towards academic performance for students. Limitations and recommendations for future studies are also discussed.